PENGARUH TEKNIK MARMET TERHADAP KELANCARAN PENGELUARAN ASI PADA IBU POST PARTUM DI RUANG NIFAS UPTD. PUSKESMAS ABIANSEMAL I - Tatik Wahyuni, Ni Wayan; Mastiningsih, Putu; Sumawati , Ni Made Risna; Yunita Udayani, Ni Putu Mirah Yunita Udayani (Universitas Prima Indonesia, 2024)
Background: Breast Milk (ASI) is considered the optimal natural nutrition for infants during the first six months of life. However, some mothers face challenges in breastfeeding due to initial low milk production and ejection, which can lead to a reluctance to breastfeed. The marmet technique, a manual breast milk expression method, aims to stimulate the Milk Ejection Reflex and increase milk supply. This study investigates the impact of the marmet technique on breast milk expression in postpartum mothers at the Abiansemal I Public Health Center's postnatal room. Objective: The primary objective of this research is to assess the effect of the marmet technique on the smoothness of breast milk expression in postpartum mothers. Method: This study employs a quasi-experimental research design with a nonequivalent control group. The sample consists of 40 postpartum mothers who were selected through purposive sampling. Data analysis is conducted using the Mann-Whitney test to determine the impact of the marmet technique on breast milk expression. Results: The statistical analysis, conducted using the Mann-Whitney test, yielded a p-value of 0.005 (p<0.05), indicating the rejection of the null hypothesis (Ho). This result implies that the marmet technique has a significant effect on improving the smoothness of breast milk expression in postpartum mothers at the Abiansemal I Public Health Center. Conclusion: In conclusion, this study demonstrates that the marmet technique is an effective method to enhance the smoothness of breast milk expression in postpartum mothers. It is recommended that postpartum mothers consider adopting the marmet technique to facilitate breastfeeding and improve milk supply.